EXPLORING ELEMENTARY SCHOOL STUDENTS’ PERCEPTION OF USING THE “GAMESTOLEARNENGLISH” WEB GAME FOR VOCABULARY LEARNING - Loreana, Yurike Risa; Irawan, Nico; Ghofur, Abd; Pramujiono, Agung (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2024)
This study investigates elementary school students' perceptions of the web-based game “gamestolearnenglish” for vocabulary learning. The game is intended to improve vocabulary utilization, motivation, and engagement by including gamification elements. Using a qualitative study, the data was collected through interviews and observations with five fifth-grade students in Surabaya who utilized the game during English learning sessions. The results indicate that the interactive features of the game significantly enhanced student motivation and facilitated an enjoyable learning experience. On the other hand, difficulties such as inadequate material variety and technological problems associated with internet connectivity were found. The game can become a more efficient tool for learning vocabulary if developed further. This study offers valuable insights for teachers and developers of digital learning tools, enabling them to design more engaging and efficient student learning experiences.